Synthesis and characterization of novel 4-aminobenzoate interleaved with zinc layered hydroxide for potential sunscreen application - Mazlina Musa (Tanjong Malim, 2019)
Synthesis and characterization of novel 4-aminobenzoate interleaved with zinc layered hydroxide for potential sunscreen application by Mazlina Musa